Impact of Intravitreal Dexamethasone Implant on Vessel Diameters in Patients with Retinal Vein Occlusion - Busra Yilmaz Tugan; Levent Karabas; Berna Ozkan (Journal of Ophthalmology)
Purpose. To investigate the vasomotor responses and diameter of retinal vessels in patients with macular edema secondary to retinal vein occlusion (RVO) who were treated with intravitreal dexamethasone implant. Methods. We enrolled 17 eyes of 17 patients with macular edema secondary to RVO. All patients were evaluated through optical coherence tomography and dynamic and static retinal vessel analysis, using the Dynamic Vessel Analyzer (Imedos, Jena, Germany) before administration (baseline) and 1 week, 1 month, and 2 months after administration of intravitreal dexamethasone. Measurements of patients were compared to those of 17 eyes of age- and sex-matched control subjects. Results. In static analysis, arteriovenous ratio (AVR) in control subjects was 0.86 (0.80–0.88). In RVO patients, baseline AVR was 0.71 (0.54–0.84) and significantly lower than that in control subjects (p=0.016). Baseline AVR in the RVO group was significantly lower than AVR at month 1 and month 2 (p=0.001 and p<0.001, respectively). CRVE in healthy control subjects was 183.59 ± 21.79 measurement units (MU) which was significantly different from CRVE of RVO eyes at baseline (207.00 ± 26.35 MU) (p=0.008). Static analysis showed a significant decrease of central retinal vein equivalent (CRVE) from baseline to 1 week, 1 month, and 2 months (p<0.001, p<0.001, and p<0.001, respectively). CRAE in the control group was 176.24 ± 22.45 MU. CRAE in the RVO group was significantly lower at baseline, week 1, month 1, and month 2 compared to that in the control group (p=0.008, p=0.003, p=0.013, and p=0.011, respectively). Dynamic analysis showed that maximum venous and arterial dilations did not statistically differ from baseline to 1 week, 1 month, or 2 months. Conclusion. Using the Dynamic Vessel Analyzer, we found that retinal veins in patients with RVO were significantly larger compared to those in the control group, and intravitreal dexamethasone treatment reduced the diameters of these veins.